النظام القانوني للرقابة والضبط الجمركية باستخدام التكنولوجيا الحديثة: The legal system for customs control using modern technology - Al Ali , Mohammad Abdallah Mohamed; Dr. Hasnizam bin Hashim,; Dr. Mohamed Nizam bin Awang, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث يهدف البحث إلى تحليل النظام القانوني للضبط الجمركي في دولة الإمارات العربية المتحدة وخاصة أن التشريعات في دولة الإمارات العربية المتحدة لم تنظم مسألة التفتيش الجمركي في قانون خاص بها، بل يتم الرجوع فيها للقواعد العامة للتفتيش في قانون الإجراءات الجزائية الاتحادي. إن الفجوة الخاصة بالدراسة الحالية هي غياب وجود تشريع خاص بتنظيم إجراءات الضبط والتفتيش واستخدام التكنولوجيا الحديثة في أعمال الضبط في الجرائم الجمركية، حيث أن الضبط والتفتيش الجمركي يخضع لإجراءات إدارية عن طريق اللوائح والأنظمة ولا يحتكم لقانون خاص. إن الدراسة تستهدف القائمين على الضبط الجمركي في المنافذ البرية والبحرية والجوية في دولة الإمارات العربية المتحدة، ورجال القانون من محامين ومستشارين قانونية وأيضاً المفتشين الجمركيين، وكذلك جهات الضبط الإداري في هذه المنافذ. ويعتمد الباحث على هذا المنهج في تحليل اللوائح والانظمة الخاصة بالضبط والتفتيش الجمركي في دولة الامارات العربية المتحدة والمقارنة بين القانون الاتحادي رقم (38) لسنة 2022 بشأن الإجراءات الجزائية والقوانين المحلية ومقارنته بما هو معمول به في دولة جمهورية مصر العربية. ABSTRACT: The research aims to analyse the legal system of customs control in the United Arab Emirates, especially that the legislation in the United Arab Emirates did not regulate the issue of customs inspection in its own law, but rather refers to the general rules of inspection in the Federal Code of Criminal Procedure. The gap of the current study is the absence of legislation regulating seizure and inspection procedures and the use of artificial intelligence entities in seizure work in customs crimes, as customs seizure and inspection are subject to administrative procedures through regulations and regulations and are not governed by a special law. The study targets customs officers at land, sea and airports in the United Arab Emirates, jurists, lawyers and legal consultants, as well as customs inspectors. As well as the administrative control bodies in these ports. The researcher relies on this approach in analyzing the regulations and regulations for customs control and inspection in the United Arab Emirates and comparing Federal Law No. (38) Of 2022 regarding criminal procedures and local laws and comparing it with what is in force in the State of the Arab Republic of Egypt.